Novel naphthalimide derived fluorescent probe based on aggregation-induced emission for turn-on detection of hydrogen sulfide. (12th February 2021) - Liu, Liqiang; Qu, Hongmei; Li, Xiaomin; Zhou, Xiaolu; Zhang, Jiacai; Sun, Yiping; Cheng, Jinxi; Zhou, Lishan
Abstract: Two novel aggregation-induced emission (AIE) based fluorescent probes, TPANI-DNs and PCZNI-DNs, have been designed and synthesized for "turn-on" detection of H2 S. Chromophore napthalimide fused triphenylamine (or phenylcarbazole) unit as fluorophore in combination with 2, 4-dinitrobenzenesulfonyl as recognition moiety constructed probes. The design strategy of the twisted D-π-A structure can efficiently transform the aggregation-caused quenching (ACQ) system into the AIE system by strengthening the restriction of intramolecular motion and preventing the intermolecular π-π stacking. The consequences showed that both TPANI-DNs and PCZNI-DNs displayed large stokes shift (135 nm and 120 nm, respectively), high selective and sensitive detection. The response mechanisms and fluorescent properties were further investigated through the time-dependent density functional theory (TDDFT). Importantly, since the strong AIE properties, a H2 S test board has been prepared and used to detect H2 S onsite easily and sensitively, displaying potential practical applications. Graphical abstract: Image 1 Highlights: Development of two novel aggregation-induced emission (AIE) based fluorescent probes for "turn-on" detection of H2 S. Two probes based on naphthalimide fused triphenylamine and phenylcarbazole possess the twisted D-π-A structure. Two probes exhibit easy synthesis, high sensitivity and specificity for H2 S. Probes are capable to detect H2 S in real water samples, and the test board can sensitive and facile detect H2 S onsite.